Everything You Always Wanted to Know about WTO Accession (But Were Afraid to Ask) - Cattaneo, Olivier (2012)
In this paper, the authors explore the complex, long, and unique process of accession to the World Trade Organization, with its intertwined economic, legal, and political dimensions. Referring to country case studies and sector-specific issues, the paper organizes some of the current reflections on the topic around three main themes. First, it explores the rationale of accession to the World Trade Organization: Why would new members join the WTO? And why would incumbent members let new members in? Second, it analyzes the World Trade Organization accession process in detail: What are the main characteristics and challenges of the accession process? Has it evolved over time, and how? Third, the paper looks at the implementation of World Trade Organization accession deals: Is accession the end or the beginning of the story? What are the implications for the participating countries and the multilateral trading system?